SOSIALISASI PENINGKATAN KEMAMPUAN BAHASA INGGRIS MELALUI PERMAINAN ONLINE - Lakuana, Nurhaida; Lebagi, Desrin; Dermawan, Dwi Wahyu (LPPM Institut Pendidikan Nusantara Global, 2024)
Online games are a form of game played over the internet network. Players can connect with other players from various geographic locations to interact and compete virtually. The aim of this research is to socialize online games to improve the English language skills of SMP Cokroaminoto Luwuk students. By applying interview techniques and summarizing the results of video recordings, it can be concluded that online games have a significant impact in improving English language skills. The effect is manifested in students' ability to learn and practice English language skills, including speaking, reading, listening, and writing skills. Therefore, games become an effective means of learning and developing English language skills for participants, helping them increase their proficiency in the language.